2004
DOI: 10.1080/00016480410022516
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of biofilm formation by dairy products and N-Acetylcysteine on voice prostheses in an artificial throat

Abstract: These in vitro experiments demonstrate that biofilm formation on voice prostheses is reduced in an artificial throat by the use of buttermilk, Yakult Light fermented milk drink and N-acetylcysteine. However, the structural differences between the type of voice prostheses may influence the ultimate effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…Sonication was capable of detaching more bacteria than the NAC and scraping methods, thus confirming the usefulness of this method reported in clinical studies [4,12,23,[28][29][30]. Some studies [2,10,16,26,33] have shown that NAC alone or in combination with other compounds has strong activity against bacterial biofilm, and the mechanism involving the disruption of biofilm may induce the susceptibility of bacteria during antibiotic Fig. 9A-H Confocal laser scanning microscopy shows the formation and removal of biofilms on prosthetic materials for S aureus on PE discs (Stains: bacteria were stained green by Syto-9, the biofilm matrix was stained red by FilmTracer TM SYPRO Ruby Matrix Stain; original magnification, x 3000).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Sonication was capable of detaching more bacteria than the NAC and scraping methods, thus confirming the usefulness of this method reported in clinical studies [4,12,23,[28][29][30]. Some studies [2,10,16,26,33] have shown that NAC alone or in combination with other compounds has strong activity against bacterial biofilm, and the mechanism involving the disruption of biofilm may induce the susceptibility of bacteria during antibiotic Fig. 9A-H Confocal laser scanning microscopy shows the formation and removal of biofilms on prosthetic materials for S aureus on PE discs (Stains: bacteria were stained green by Syto-9, the biofilm matrix was stained red by FilmTracer TM SYPRO Ruby Matrix Stain; original magnification, x 3000).…”
Section: Discussionsupporting
confidence: 64%
“…Sonication of explanted implants has notably improved sensitivity of microbiologic diagnosis of PJIs by dislodging bacteria from biofilm adhered to prosthetic surfaces, as documented in numerous studies [1,4,12,13,23,[28][29][30]. Since NAC exerts activity against bacterial biofilms [2,10,16,26,33], we presumed NAC and DTT could be used to remove bacteria from a prosthetic biofilm. We asked the following questions: (1) Do DTT and NAC remove bacteria from biofilm formed on prosthetic materials?…”
Section: Discussionmentioning
confidence: 99%
“…Pérez-Giraldo et al (1997) studied the influence of various concentrations of N-acetylcysteine on the formation of biofilms of different strains of Staphylococcus epidermidis and found a dose-related decrease in biofilm and slime formation. Schwandt et al (2004) inoculated Groningen button and Provox2 VPs with a mixture of bacteria and yeasts. On Groningen button VPs Nacetylcysteine reduced the amount of bacteria and yeasts to 2.4 % (P,0.01) and 55 % (P,0.15) of the control value, respectively.…”
Section: Prophylactic Treatment Of Silicone Rubber Voice Prosthesesmentioning
confidence: 99%
“…These properties may contribute to the prevention and disruption of biofilm around different polymeric and metallic surfaces (9,(19)(20)(21). Not only does NAC diminish the formation of biofilm by common pathogens (19,22,23), it also possesses some in vitro intrinsic antimicrobial activity against both Gram-positive and Gram-negative bacteria (24). Taking into consideration the therapeutic safety record and the antibiofilm ability of NAC combined with antimicrobial activity of a broad-spectrum antibiotic, impregnation of intravascular catheters with this unique combination can be a promising approach for reducing catheter colonization and potential subsequent catheter-associated infection.…”
mentioning
confidence: 99%